Research on blood donation and supply of red blood cell products to medical institutions under the spread of COVID-19 disease in Japan - Tomohide Mishiba; Shinji Takeoka (Heliyon)
Due to the spread of SARS-CoV-2 virus infectious disease (COVID-19), blood donation events had to be cancelled, and there were concerns about a decrease in the number of blood donors from late February 2020 in Japan. The purpose of this study is to investigate the numbers of whole blood donation, manufacture and inventory adjustment of red blood cell (RBC) products at the Japanese Red Cross Society (JRCS), and to evaluate the effects of COVID-19 on the donation of blood and the supply of RBC products to medical institutions for transfusion medicine in Japan. We focused on RBC products, which are the most frequently used blood products and are easily reflected under the spread of COVID-19. The status of whole blood donation and RBC product transfusion was investigated based on the data provided by the JRCS from January 2020 to August 2021 on whole blood donation, manufacture and inventory adjustment of RBC products, and supply to medical institutions. Although there were some fluctuations since January 2020, the amount of estimated donated whole blood, manufactured RBC products, inventory, and supply to medical institutions remained almost stable. The reasons are thought to be the contribution of registered repeaters cooperating in blood donation, the accurate prediction of supply and demand by the JRCS, the call for blood donations in accordance with the prediction, and the timely exchange of products between block centers, and the utilization of a safe supply system established previously by the JRCS. As a result, it can be concluded that the stable provision of medical care was possible without depleting the inventory of RBC products even under the spread of COVID-19.